ESTRATÉGIAS DE PREVENÇÃO E ADESÃO AOS TRATAMENTOS DE DOENÇAS CARDIOVASCULARES: UMA REVISÃO NARRATIVA (REMUNOM, 2025)
Introduction: Cardiovascular diseases, in general, constitute the largest public health cost in the world. In Brazil alone, a country of continental dimensions marked by profound socioeconomic inequalities, in the last 10 years, the cost to the public coffers of hospitalizations and interventions related to cardiovascular diseases was more than 35 billion reais, which could be drastically reduced through prevention strategies and adequate adherence to treatment by patients. Objective: To conduct a narrative review of the literature capable of demonstrate evaluating prevention strategies and adherence to treatments for cardiovascular diseases in Brazil and worldwide. Results and discussion: In the sample analyzed, it was possible to observe that the outcomes related to adherence to treatment, as well as the prevention of cardiovascular diseases, can be improved through health education strategies that aim to meet the needs of each population group, ensuring that equity continues to be one of the pillars for access to quality public health. Studies have shown that the main barriers to non-adherence to treatment are mainly related to the lack of knowledge about the disease by the patient or family, and that this, combined with financial and travel difficulties, become an important factor in non-adherence to prescribed treatments. Conclusion: Given the barriers observed and the strategies used in some studies to overcome these conditions, it is noted that the vicious cycle of overloading the health system and excessive public spending on cardiovascular diseases can be controlled with adequate planning.